The influence of anxiety on students' oral evaluations in the readings and conversation i course at the Foreign Languages Department - Mejía Coreas, Ana Ruth; Santamaria Rivas, Mariela Melissa; Reyes de Amaya, Cecilia del Carmen; Garay Salinas, Ricardo (San Salvador : Universidad de El Salvador, 2013)
This study was designed in order to investigate how anxiety affects students’ oral evaluations in the Readings and Conversation I course at the Foreign Languages Department of the University of El Salvador. A total of 99 students participated in the study as a sample to answer the survey administered to gather the data related to anxiet y. This survey consisted in a 1 to 5 point scale, which was used by students to judge some statements related to anxiety. A total of 39 students were the sample for the second instrument applied, that is, the checklist. This was used to measure the levels of anxiety of students during their oral participations during a day-to-day class. This instrument was used in order to contrast the experiences of students when participating in oral activities during class, where they are not graded directly, with their erformance during oral evaluations, when they are aware that they have a grade to get. These 39 students were interviewed as well, to obtain a direct account of the ir experience after the oral evaluation. The six teachers in charge of this course were interviewed as well, in order to gain some insight on how they see their students’ oral performances when evaluating them. The teachers’ responses were of great importa nce to highlight the problems they see when evaluating their highly stressed students, they notice how this affects their oral performance, and shared some strategies they implement to alleviate this situation.
Tesis -- (Licenciatura en Idioma Inglés, opción Enseñanza) -- Universidad de El Salvador, San Salvador, 2013
Bibliografía : hojas 62-65
Audiencia general
Keywords: Lenguaje y lenguas -- Enseñanza; Lectura -- Aspectos psicológicos; Ansiedad; Evaluación